Guanonisa reduz a neurotoxicidade e o déficit motor induzido pelo traumatismo cranioencefálico em ratos - Gerbatin, Rogério da Rosa (2016)
Traumatic brain injury (TBI) affects annually 10 million of people causing neurological symptoms and deaths resulting in an adverse socio-economic impact worldwide. The pathophysiology of TBI comprises multiple neurotoxic processes, such as excitotoxicity, mitochondrial dysfunction and inflammation leading to neuronal death and consequently clinical manifestations, as motor deficit. Many studies with promising drugs in experimental models of TBI reported failures in clinical tests, so it is important to search for new therapeutic drugs. Currently, much attention has been devoted to the neuroprotective effects of guanosine, an endogenous nucleoside able to reduce neurotoxic events in experimental models of ischemia in vivo and in vitro, which to our knowledge has not yet been evaluated in the TBI. Therefore, the present study evaluated the therapeutic potential of guanosine in locomotor impairment and neurodegeneration after TBI by controlling excitotoxicity, mitochondrial and inflammatory alterations. Male Wistar rats were subjected to TBI by moderate fluid percussion injury (PFS) parasagittal model and 40 minutes after was administered guanosine (7.5mg / kg intraperitoneally). Our results show that guanosine protects against the locomotor deficit induced by TBI 8 hours after the insult. Similarly, guanosine was also able to protect against the neurochemical damage in the ipsilateral cortex characterized by the inhibition of glutamate uptake, Na+, K+ - ATPase and glutamine synthetase activity , alterations in mitochondrial membrane potential (ΔѰm) followed by an increase in production of reactive species oxygen (ROS) and content of protein carbonyls. Furthermore, the inflammatory response induced by TBI evidenced by increased levels of TNF-α, IL-1β and cerebral edema was also reduced by guanosine. In addition to these findings, guanosine protected against the neuronal death and activation of caspase 3, reinforcing its neuroprotective effects. Thus, our study represents an important contribution to the knowledge of the neuroprotective effects of guanosine in the TBI, making this an attractive candidate molecule for the treatment of this insult, although more studies are needed to clarify their potential in clinical TBI.